A CONTENT ANALYSIS OF ENGLISH TEXTBOOK ENTITLED “WHEN ENGLISH RINGS A BELL” - Widyastuti, Iin; Syam, Andi Tenrisanna; Yahya, Amalia (FKIP Unismuh Makassar, 2024)
The purpose of this research is to evaluate the suitability of the materials in the English textbook titled